2016
DOI: 10.1016/j.ijpvp.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A study on the evolution of the contact angle of small punch creep test of ductile materials

Abstract: The work discussed in the present paper reports a novel investigation of the applicability of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…pre L pre = yield L yield (20) Expressing equation (20) in the form of equation (21), it is possible to derive d pre as in equation (22) (22) L pre and L yield are given in equation (23) and in equation (24), respectively, where L 0 is the initial specimen gauge length.…”
Section: Plastic Part Of Pre-strainingmentioning
confidence: 99%
See 1 more Smart Citation
“…pre L pre = yield L yield (20) Expressing equation (20) in the form of equation (21), it is possible to derive d pre as in equation (22) (22) L pre and L yield are given in equation (23) and in equation (24), respectively, where L 0 is the initial specimen gauge length.…”
Section: Plastic Part Of Pre-strainingmentioning
confidence: 99%
“…During small punch creep tests however, damage starts developing in the secondary stage of the deflection versus time curve, where deformation of the specimen is dominated by dislocation creep. The tertiary region of the deflection versus time curve is characterised by an acceleration of the crack propagation and the deformation of the disk is governed by inter-granular cavitation [23, 24]. A small punch specimen generally experiences the evolution of a necking region, which takes place at an offset from the axis of symmetry of the disk [2527].…”
Section: Introductionmentioning
confidence: 99%
“…This happens when large deformations are exhibited by the specimen during the test, that is, from an engineering estimation, when Δ>0.8 mm [5]. However, according to many researchers, during small punch creep test the specimen deformation is caused by bending prior to membrane stretching [30][31][32] and a recent study, confirming this theory, suggests upper limits to Δ, depending on the specimen and the punch dimensions [33], as shown in Table 1. Another empirical relationship, always derived by Chakrabarty's membrane theory, is reported in an annex of the Code of practice [5], and can be used to derive the load to be applied for the SPCT, here given in equation (12), where KSP is a correction factor depending on the tested material.…”
Section: Small Punch Creep Testmentioning
confidence: 93%
“…Difficulties in obtaining good agreement between FE analyses and small punch test output are due to the effects on the specimen time to failure of punch load misalignments, of initial plasticity, and of the approximation of the friction formulation used in the FE analyses for the interactions between the specimens and the testing machine components [33]. An increase of the failure life has been found to be up to 10 times when initial plastic deformation is included in the model [30]; the time to failure can also increase up to 8 times when the friction coefficient between the specimen and the punch varies from 0 to 0.5 [51][52][53].…”
Section: Evaluation Of Current Test Methodsmentioning
confidence: 99%
“…Now, the question is how the contact properties influence the test results. Only a few studies have been found in literature, which explicitly focus on this problem [9][10][11][12][13]. The aim of this paper is to fill some of the gaps and to give suggestions about optimal test setups and evaluation strategies.…”
Section: Introductionmentioning
confidence: 99%